A method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel

Through rare earth ion penetration and tempering treatment and optical and partially aggregated interface image analysis of composite rare earth inclusions, the amount of rare earth elements added to high-strength tough steel is solved, and the corrosion resistance caused by inaccurate addition of rare earth in the prior art is solved. and the problem of insufficient wear resistance significantly improves the performance of alloy steel.

CN118854218BActive Publication Date: 2024-12-17INNER MONGOLIA ZHONGTIAN HONGYUAN RARE EARTH NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411328285.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

In the prior art, the amount of rare earth elements added to alloy steel is low, resulting in insufficient corrosion resistance and wear resistance of high-strength steel.

Method used

Through rare earth ion permeation and tempering treatment, the anticorrosion and wear resistance are determined using the optical image of composite rare earth inclusions and the polarization interface image, the cooling rate and the ratio of lanthanum and cerium are adjusted, and the amount of rare earth added is accurately controlled. Combined with tensile strength detection, the actual amount of rare earth added is ensured.

Benefits of technology

Improve the accuracy of the amount of rare earth added, enhance the corrosion resistance and wear resistance of high-strength steel, ensure the improvement of rare earth yield in alloy steel, reduce misjudgment and cause search time, and improve the efficiency of rare earth addition .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854218B_ABST
    Figure CN118854218B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rare earth treatment, and in particular to a method for controlling the amount of rare earth added to a rare earth low alloy high-strength and tough steel. The invention obtains an optical image of a composite rare earth inclusion formed by interaction between aluminum oxide and manganese sulfide after adding a rare earth solution through testing. The optical image of the composite rare earth inclusion can accurately determine whether the anti-corrosion performance of the high-strength and tough steel meets the standard, thereby improving the accuracy of the amount of rare earth added to the high-strength and tough steel. The image of the segregated interface of rare earth ions, lanthanum ions and cerium ions can determine whether the wear resistance of the high-strength and tough steel meets the standard, further improving the accuracy of the amount of rare earth added to the high-strength and tough steel. According to the determined amount of rare earth added, an actual rare earth ion penetration quenching and tempering treatment operation is performed on the alloy steel, thereby further improving the accuracy of the amount of rare earth added to the high-strength and tough steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rare earth processing, and in particular to a method for controlling the amount of rare earth added to rare earth low-alloy high-strength and toughness steel. Background Art

[0002] Rare earth elements are added as deoxidation and desulfurization agents, and the rare earth recovery rate in steel is less than or equal to 30%. As a deoxidation product, a part of rare earth oxides floats up, and the other part of rare earth oxides remaining in the steel may cause nozzle nodules; rare earth elements can denature inclusions and promote inclusion spheroidization. The addition of rare earth elements in steel can improve the corrosion resistance of steel. Therefore, how to improve the corrosion resistance of steel through rare earth addition control is becoming more and more important.

[0003] Prior art CN117660725B discloses a rare earth treatment method for low alloy wear-resistant steel, which is to modify the refined slag at the end of the LF refining of low alloy wear-resistant steel, and change the refined slag into a new slag system by adding rare earth oxides, lime, quartz sand, alumina, etc. The design of the new slag system reduces the reactivity between the refined slag and the rare earth in the steel, and at the same time, enhances the dissolution and absorption capacity and desulfurization capacity of inclusions. By adding rare earth-iron alloy, the rare earth content in the low alloy wear-resistant steel reaches 0.005% to 0.03%, and the formation of large-sized high melting point inclusions is suppressed, avoiding nozzle nodules in the continuous casting process. The addition of rare earth elements in steel improves the corrosion resistance of steel, but does not involve the regulation of rare earth addition of steel corrosion resistance. Summary of the invention

[0004] To this end, the present invention provides a method for controlling the amount of rare earth added to a rare earth low-alloy high-strength and toughness steel, so as to overcome the problem of low corrosion resistance and low wear resistance of the alloy steel due to the low accuracy of the actual amount of rare earth added during the refining and adding of rare earth elements in the high-strength and toughness steel in the prior art.

[0005] To achieve the above object, the present invention provides a method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel, comprising:

[0006] Step S1, applying a rare earth solution for testing to the surface of the alloy steel for rare earth ion penetration and tempering treatment to form a high-strength and toughness steel for testing;

[0007] Step S2, obtaining an optical image and a segregated interface image of the composite rare earth inclusions on the surface of the high-strength and toughness steel;

[0008] Step S3, judging whether the anti-corrosion performance of the high-strength and toughness steel meets the standard according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions;

[0009] Step S4, if it is determined that the anti-corrosion performance does not meet the standard, determining whether to increase the cooling rate in the rare earth ion penetration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions;

[0010] Step S5, if it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard, then judging whether the wear resistance of the high-strength and toughness steel meets the standard according to the segregation boundary of the lanthanum element in the segregation interface image;

[0011] Step S6, if it is determined that the wear resistance does not meet the standard, determining the ratio of lanthanum and cerium in the test rare earth solution according to the average particle size of the rare earth ions of the composite rare earth inclusions;

[0012] Step S7, detecting the tensile strength of the high-strength and tough steel, and determining the actual amount of rare earth added according to the tensile strength of the high-strength and tough steel;

[0013] Step S8, adding the actual amount of rare earth to the production rare earth solution to perform actual rare earth ion penetration modulation treatment operation on the alloy steel to output high-strength and toughness steel;

[0014] Furthermore, the rare earth ion penetration and tempering treatment process includes:

[0015] Clean the surface of the alloy steel to remove grease and dirt on the surface of the alloy steel;

[0016] Coating the surface of the alloy steel with a rare earth solution for testing to form a coated alloy steel;

[0017] Drying the surface of the coated alloy steel to form a fixed coated alloy steel;

[0018] sequentially heat treating and cooling the fixed coated alloy steel to form high-strength and toughness steel;

[0019] Wherein, the rare earth ions in the fixed coating layer have fixed distribution positions.

[0020] Further, judging whether the anti-corrosion performance of the high-strength and toughness steel meets the standard according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions includes:

[0021] Obtaining the distribution density of rare earth ions in an optical image of the composite rare earth inclusions by scanning electron microscopy;

[0022] Comparing the distribution density of the rare earth ions with a preset distribution density;

[0023] If the distribution density of the rare earth ions is greater than the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard;

[0024] If the distribution density of the rare earth ions is less than or equal to the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel does not meet the standard.

[0025] Further, judging whether the wear resistance of the high-strength and toughness steel meets the standard according to the segregation boundary of the lanthanum element in the segregation interface image includes:

[0026] The distribution uniformity of the segregation boundary of the lanthanum element was detected by scanning electron microscopy and atom probe to obtain the segregation interface image;

[0027] Comparing the distribution uniformity of the segregation boundary of the lanthanum element with a preset distribution uniformity;

[0028] If the distribution uniformity of the segregation boundary of the lanthanum element is greater than the preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel meets the standard;

[0029] If the distribution uniformity of the segregation limit of the lanthanum element is less than or equal to a preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel does not meet the standard.

[0030] Further, determining whether to increase the cooling rate in the rare earth ion infiltration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions includes:

[0031] comparing a difference between a preset distribution density and the distribution density of rare earth ions in the optical image of the composite rare earth inclusion with the preset distribution density difference;

[0032] If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is greater than the preset distribution density difference, it is determined to increase the cooling rate in the rare earth ion infiltration and tempering treatment.

[0033] Further, the increase range of the cooling rate in the rare earth ion infiltration and tempering treatment is determined by the difference between a preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions.

[0034] Further, determining the ratio of lanthanum and cerium in the rare earth solution for testing according to the average particle size of the rare earth ions of the composite rare earth inclusions includes:

[0035] comparing the average particle size of the rare earth ions with a preset average particle size;

[0036] If the average particle size of the rare earth ions is greater than the preset average particle size, the ratio of the lanthanum element to the cerium element in the rare earth solution for testing is adjusted.

[0037] Further, the process of determining the amount of rare earth added according to the tensile strength of the high-strength and tough steel includes:

[0038] comparing the tensile strength with a preset tensile strength;

[0039] If the tensile strength is less than or equal to the preset tensile strength, the actual amount of rare earth added is increased.

[0040] Furthermore, the increase range of the ratio of lanthanum element to cerium element in the test rare earth solution is determined according to the difference between the average particle size of the rare earth ions and a preset average particle size.

[0041] Furthermore, the increase in the actual amount of rare earth added is determined by the difference between the preset tensile strength and the tensile strength; the rare earth addition amount ranges from 100ppm to 400ppm; wherein the components of the composite rare earth inclusions include rare earth elements, alumina and manganese sulfide, and the components of the segregated interface include rare earth elements, lanthanum and cerium.

[0042] Compared with the prior art, the beneficial effect of the present invention is that the present invention provides a method for controlling the rare earth addition amount of rare earth low-alloy high-strength and tough steel. The present invention can form an optical image of a composite rare earth inclusion through the interaction between rare earth elements, aluminum oxide and manganese sulfide. The optical image of the composite rare earth inclusion can accurately determine whether the corrosion resistance of the high-strength and tough steel meets the standard, thereby improving the accuracy of the rare earth addition amount of the high-strength and tough steel. The segregated interface image of the rare earth elements, lanthanum elements and cerium elements can determine whether the wear resistance of the high-strength and tough steel meets the standard, reducing the occurrence of misjudgment, thereby further improving the accuracy of the rare earth addition amount of the high-strength and tough steel. At the same time, the segregated interface image of the rare earth elements, lanthanum elements and cerium elements can accurately determine whether the addition amount of the rare earth elements is in compliance with the standard. The method of adding rare earths saves the time of finding the cause and improves the efficiency of adding rare earths to high-strength and tough steel. Moreover, when it is determined that the method of adding rare earths is to adjust the ratio of lanthanum and rare earth elements, the amount of lanthanum added can be accurately determined by the average particle size of the composite rare earth inclusions. The present invention can accurately perform rare earth ion penetration and tempering treatment by determining the amount of lanthanum added. At the same time, the amount of rare earth added can be determined according to the tensile strength of the high-strength and tough steel after the rare earth ion penetration and tempering treatment. The alloy steel is actually subjected to rare earth ion penetration and tempering treatment according to the determined rare earth addition amount, thereby further improving the accuracy of the rare earth addition amount of the high-strength and tough steel. The present invention improves the corrosion resistance and wear resistance of the high-strength and tough steel by adding the rare earth ion penetration and tempering treatment.

[0043] Furthermore, the present invention overcomes the problem that the rare earth recovery rate in alloy steel does not exceed 30% when rare earth elements are added as deoxidation and desulfurization agents. The present invention improves the corrosion resistance of alloy steel by regulating inclusions. After the rare earth elements are added, aluminum oxide and manganese sulfide form composite rare earth inclusions and spheroidize, which changes the properties and morphology of the inclusions and reduces the electrode potential difference between the inclusions and the matrix. Therefore, the self-corrosion point and polarization resistance of the alloy steel are significantly improved. By accurately adjusting the addition amount of rare earth lanthanum and cerium elements in the range of 100ppm to 400ppm, the rare earth recovery rate in alloy steel reaches more than 79%. The present invention improves the rare earth recovery rate in alloy steel by controlling the amount of rare earth added to high-strength and tough steel.

[0044] Furthermore, the present invention overcomes the problem that the physical and chemical detection methods have temporarily failed to solve the mechanism of action of solid solution and precipitation of rare earth elements. The present invention detects that the atomic radius of rare earth lanthanum is 2.74Å, the atomic radius of cerium is 2.7Å, and the atomic radius of iron is 1.72Å. The energy required for large-sized rare earth atoms to solid-dissolve in the lattice by replacing iron atoms is high. Primary atomic calculation, SMS and other methods confirm that large rare earth lanthanum and cerium atoms tend to be segregated at grain boundaries and phase boundaries with higher energy, unstable arrangement and more defects, which significantly reduces the interface energy and reduces the occurrence of local corrosion.

[0045] Furthermore, the present invention increases the bonding force and adhesion strength between the rust layer and the substrate by adding rare earth elements to the high-strength and toughness steel, thereby improving the compactness of the rust layer and the corrosion resistance of the high-strength and toughness steel.

[0046] Furthermore, the present invention accurately determines that the lanthanum and cerium elements are concentrated at the interface between the rust layer and the substrate through a scanning electron microscope. As the corrosion time increases, the lanthanum and cerium elements participate in the formation of composite oxides in the rust layer to form stable rare earth oxides, thereby improving the protection capability of the alloy steel.

[0047] Furthermore, the present invention increases the frequency of alternation of large and small cycles of the cooling medium, thereby increasing the cooling rate, reducing the low stability of the distribution density of composite rare earth inclusions caused by inconsistent cooling rates of the inner and outer layers during the cooling process, thereby further improving the accuracy of the rare earth addition amount of high-strength and toughness steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A flow chart of the steps of a method for controlling the amount of rare earth added to a rare earth low alloy high-strength and toughness steel according to an embodiment;

[0049] Figure 2 The present invention is a flow chart for determining whether the anti-corrosion performance of rare earth low alloy high-strength and toughness steel meets the standards;

[0050] Figure 3 This is an optical image of composite rare earth inclusions on the surface of high-strength and tough steel in the embodiment;

[0051] Figure 4 This is an image of the segregated interface of composite rare earth inclusions on the surface of high-strength and toughness steel in the example. DETAILED DESCRIPTION

[0052] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0053] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0054] It should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0055] In addition, it should be noted that in the description of the present invention, it should also be noted that the data in this embodiment are obtained by comprehensive analysis and evaluation of the historical test data and the corresponding historical test results of the system of the present invention in the three months before this test. The system of the present invention comprehensively determines the values ​​of the preset parameter benchmarks for this test based on the results of the cumulative tests in the previous three months before this test. It can be understood by those skilled in the art that the determination method of the system of the present invention for a single item of the above parameters can be to select the value with the highest proportion as the preset benchmark parameter according to the data distribution, use weighted summation to use the obtained value as the preset benchmark, use the value of each historical data as the preset benchmark parameter or other selection methods, as long as the system of the present invention can clearly define the different specific situations in the single determination process through the obtained values.

[0056] See also Figure 1 , Figure 2 , Figure 3 and Figure 4As shown, they are respectively a flow chart of the steps of the method for controlling the amount of rare earth added to the rare earth low alloy high-strength and tough steel of the embodiment; a flow chart for determining whether the anti-corrosion performance of the rare earth low alloy high-strength and tough steel of the embodiment meets the standard; an optical image of the composite rare earth inclusions on the surface of the high-strength and tough steel of the embodiment; an image of the segregated interface of the composite rare earth inclusions on the surface of the high-strength and tough steel of the embodiment; a method for controlling the amount of rare earth added to the rare earth low alloy high-strength and tough steel of the embodiment of the present invention, comprising:

[0057] Step S1, applying a rare earth solution for testing to the surface of the alloy steel for rare earth ion penetration and tempering treatment to form a high-strength and toughness steel for testing;

[0058] Step S2, obtaining an optical image and a segregated interface image of the composite rare earth inclusions on the surface of the high-strength and toughness steel;

[0059] Step S3, judging whether the anti-corrosion performance of the high-strength and toughness steel meets the standard according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions;

[0060] Step S4, if it is determined that the anti-corrosion performance does not meet the standard, determining whether to increase the cooling rate in the rare earth ion penetration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions;

[0061] Step S5, if it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard, then judging whether the wear resistance of the high-strength and toughness steel meets the standard according to the segregation boundary of the lanthanum element in the segregation interface image;

[0062] Step S6, if it is determined that the wear resistance does not meet the standard, determining the ratio of lanthanum and cerium in the test rare earth solution according to the average particle size of the rare earth ions of the composite rare earth inclusions;

[0063] Step S7, detecting the tensile strength of the high-strength and tough steel, and determining the actual amount of rare earth added according to the tensile strength of the high-strength and tough steel;

[0064] Step S8, adding the actual amount of rare earth added to the production rare earth solution to perform actual rare earth ion penetration modulation treatment operation on the alloy steel to output high-strength and toughness steel.

[0065] Specifically, the rare earth addition control of rare earth low-alloy high-strength and toughness steel includes a central control processor, which is a PLC controller, and sends the control or parameter adjustment signals of the corresponding equipment and the ratio adjustment information to the corresponding equipment and the mobile terminal, which can be a mobile phone.

[0066] In practice, the composite rare earth inclusions are formed by the interaction between the rare earth elements, alumina and manganese sulfide, and the segregated interface is formed by the rare earth elements, lanthanum elements and cerium elements.

[0067] In implementation, the optical image of the composite rare earth inclusions is determined by a scanning electron microscope and an electron probe, and the segregation interface image of the rare earth elements, lanthanum elements and cerium elements is determined by an Auger spectrometer and a scanning electron microscope. The optical image of the composite rare earth inclusions can be formed by the interaction between the rare earth elements, alumina and manganese sulfide. The optical image of the composite rare earth inclusions can accurately determine whether the amount of rare earth elements added meets the standard, thereby improving the accuracy of the rare earth addition amount of high-strength and tough steel. The segregation interface image of the rare earth elements, lanthanum elements and cerium elements can be used to secondarily determine whether the amount of rare earth elements added meets the standard, reducing the occurrence of misjudgment, thereby further improving the accuracy of the rare earth addition amount of high-strength and tough steel. At the same time, the segregation interface image of the rare earth elements, lanthanum elements and cerium elements can accurately determine the reason why the amount of rare earth elements added does not meet the standard, saving the time for finding the cause and improving the accuracy of the rare earth addition amount of high-strength and tough steel. The efficiency of rare earth addition in high-strength and tough steel is improved. Moreover, in the case of the lanthanum-cerium ratio of lanthanum and cerium, the amount of lanthanum added can be accurately determined by the average particle size of the composite rare earth inclusions, further improving the accuracy of rare earth addition in high-strength and tough steel. The present invention can accurately perform rare earth ion penetration tempering treatment by determining the amount of lanthanum added. At the same time, the amount of rare earth added can be accurately determined according to the tensile strength of the high-strength and tough steel after the rare earth ion penetration tempering treatment. The rare earth ion penetration tempering treatment operation is performed on the rare earth alloy high-strength and tough steel according to the determined amount of rare earth added. The present invention improves the accuracy and corrosion resistance of high-strength and tough steel by adding rare earth ion penetration tempering treatment.

[0068] Specifically, the rare earth ion penetration and tempering process includes:

[0069] Clean the surface of the alloy steel to remove grease and dirt on the surface of the alloy steel;

[0070] Coating the surface of the alloy steel with a rare earth solution for testing to form a coated alloy steel;

[0071] Drying the surface of the coated alloy steel to form a fixed coated alloy steel;

[0072] sequentially heat treating and cooling the fixed coated alloy steel to form high-strength and toughness steel;

[0073] Wherein, the rare earth ions in the fixed coating layer have fixed distribution positions.

[0074] During implementation, the temperature of the heat treatment process is 800℃~900℃, the heat treatment time is 2 hours~5 hours, and the cooling method uses a large circulation and a small circulation of the cooling medium to alternate with each other to achieve the cooling effect. When the frequency of alternation of the large circulation and the small circulation of the cooling medium increases, the cooling rate can be increased, thereby increasing the cooling rate and reducing the low stability of the distribution density of the composite rare earth inclusions caused by the inconsistent cooling rates of the inner and outer layers during the cooling process, thereby further improving the accuracy of the rare earth addition amount of the high-strength and toughness steel.

[0075] In practice, the present invention overcomes the problem that the rare earth recovery rate does not exceed 30% when rare earth elements are added to alloy steel as deoxidation and desulfurization agents. The present invention improves the corrosion resistance of alloy steel by regulating inclusions. After the rare earth elements are added, aluminum oxide and manganese sulfide form composite rare earth inclusions and spheroidize, which changes the nature and morphology of the inclusions and reduces the electrode potential difference between the inclusions and the matrix. Therefore, the self-corrosion point and polarization resistance of the alloy steel are significantly improved. By accurately adjusting the addition amount of rare earth lanthanum and cerium elements in the range of 100ppm to 400ppm, the rare earth recovery rate in alloy steel reaches more than 79%. The present invention improves the rare earth recovery rate in alloy steel by controlling the amount of rare earth added to high-strength and tough steel.

[0076] Specifically, the central control processor determines whether the corrosion resistance of the high-strength and toughness steel meets the standard based on the distribution density of rare earth ions in the optical image of the composite rare earth inclusions, wherein the central control processor is a PLC controller, and sends the control or parameter adjustment signals of the corresponding equipment and the ratio adjustment information to the corresponding equipment and the mobile terminal, wherein the central control processor is a PLC controller and the mobile terminal can be a mobile phone.

[0077] Specifically, judging whether the anti-corrosion performance of high-strength and toughness steel meets the standard according to the distribution density of rare earth ions in the optical image of the composite rare earth inclusions includes:

[0078] Obtaining the distribution density of rare earth ions in an optical image of the composite rare earth inclusions by scanning electron microscopy;

[0079] Comparing the distribution density of the rare earth ions with a preset distribution density;

[0080] If the distribution density of the rare earth ions is greater than the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard;

[0081] If the distribution density of the rare earth ions is less than or equal to the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel does not meet the standard.

[0082] In implementation, the composite rare earth inclusion distribution density is preset to 90%. The present invention overcomes the problem that the physical and chemical detection method has temporarily failed to solve the mechanism of action of solid solution and precipitation of rare earth elements. The present invention detects that the atomic radius of rare earth lanthanum is 2.74Å, the atomic radius of cerium is 2.7Å, and the atomic radius of iron is 1.72Å. The energy required for large-sized rare earth atoms to solid-dissolve in the lattice by replacing iron atoms is high. Primary atomic calculations, SMS and other methods have confirmed that large rare earth lanthanum and cerium atoms tend to be segregated at grain boundaries and phase boundaries with higher energy, unstable arrangement and more defects, which significantly reduces the interface energy and reduces the occurrence of local corrosion.

[0083] Specifically, the central control processor determines whether the wear resistance of the high-strength and tough steel meets the standard based on the segregation boundary of the lanthanum element in the segregation interface image, wherein the central control processor is a PLC controller, and sends the control or parameter adjustment signals of the corresponding equipment and the ratio adjustment information to the corresponding equipment and the mobile terminal, wherein the central control processor is a PLC controller and the mobile terminal can be a mobile phone.

[0084] Specifically, judging whether the wear resistance of high-strength and tough steel meets the standard based on the segregation boundary of the lanthanum element in the segregation interface image includes:

[0085] The distribution uniformity of the segregation boundary of the lanthanum element was detected by scanning electron microscopy and atom probe to obtain the segregation interface image;

[0086] Comparing the distribution uniformity of the segregation boundary of the lanthanum element with a preset distribution uniformity;

[0087] If the distribution uniformity of the segregation boundary of the lanthanum element is greater than the preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel meets the standard;

[0088] If the distribution uniformity of the segregation limit of the lanthanum element is less than or equal to a preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel does not meet the standard.

[0089] The distribution uniformity of the segregation boundary of the lanthanum element in the segregation interface image is the distribution percentage of the lanthanum element per unit area, and the preset distribution uniformity is 90%.

[0090] Specifically, the central control processor determines whether to increase the cooling rate in the rare earth ion penetration tempering treatment according to the distribution density of rare earth ions in the optical image of the composite rare earth inclusions, and sends the control or parameter adjustment signal of the corresponding equipment and the information of the ratio adjustment to the corresponding equipment and the mobile terminal, wherein the central control processor is a PLC controller and the mobile terminal can be a mobile phone.

[0091] Specifically, determining whether to increase the cooling rate in the rare earth ion infiltration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions includes:

[0092] comparing a difference between a preset distribution density and the distribution density of rare earth ions in the optical image of the composite rare earth inclusion with the preset distribution density difference;

[0093] If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is greater than the preset distribution density difference, it is determined to increase the cooling rate in the rare earth ion infiltration and tempering treatment.

[0094] Specifically, the increase range of the cooling rate in the rare earth ion penetration and tempering treatment is determined by the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions, including:

[0095] If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is less than or equal to a preset first distribution density difference, the cooling rate is increased using a first adjustment coefficient γ1;

[0096] If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is greater than the preset first distribution density difference and less than or equal to the preset second distribution density difference, the cooling rate is increased using the second adjustment coefficient γ2;

[0097] If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is greater than the preset second distribution density difference, the cooling frequency is increased using the third adjustment coefficient γ3;

[0098] In implementation, the first distribution density difference is preset to be 5%; the second distribution density difference is preset to be 10%, and the formula for increasing the cooling rate is f=f0×(1+γn) / 2, where f is the cooling rate after adjustment, and f0 is the cooling rate before adjustment. In implementation, the cooling medium is water, and the cooling rate of the cooling medium before adjustment is 50 times / minute, wherein γ1=1.12; γ2=1.16; γ3=1.20; if the inclusion distribution density of rare earth ions in the optical image of the composite rare earth inclusions is 86%, the difference between the preset distribution density and the distribution density of rare earth ions in the optical image of the composite rare earth inclusions is 4%, so the cooling rate of the cooling medium is increased to f=f0×(1+γn) / 2=50×(1.12+1) / 2=53 / minute.

[0099] In implementation, the cooling medium may be one or two of water, solvent, air, nitrogen, oil, ethylene glycol, propylene glycol, and brine.

[0100] Specifically, the ratio of lanthanum and cerium in the rare earth solution for testing is determined according to the average particle size of the rare earth ions of the composite rare earth inclusions, including:

[0101] The average particle size of the rare earth ions in the composite rare earth inclusions was collected using a scanning electron microscope;

[0102] comparing the average particle size of the rare earth ions with a preset average particle size;

[0103] If the average particle size of the rare earth ions is greater than the preset average particle size, the ratio of the lanthanum element to the cerium element in the rare earth solution for testing is adjusted.

[0104] In practice, the preset average particle size is 2.0 μm. The present invention increases the bonding force and adhesion strength between the rust layer and the substrate by adding rare earth elements to the high-strength and toughness steel, improves the compactness of the rust layer and improves the corrosion resistance of the high-strength and toughness steel.

[0105] Specifically, the process of determining the amount of rare earth addition based on the tensile strength of high-strength and tough steel includes:

[0106] comparing the tensile strength with a preset tensile strength;

[0107] If the tensile strength is less than or equal to the preset tensile strength, the actual amount of rare earth added is determined.

[0108] In implementation, the preset tensile strength is 1000 MPa.

[0109] Specifically, the increase range of the ratio of lanthanum element to cerium element in the test rare earth solution is determined according to the difference between the average particle size of the rare earth ions and the preset average particle size.

[0110] The adjustment process of adding lanthanum and cerium elements includes:

[0111] If the difference between the average particle size of the rare earth ions and the preset average particle size is less than or equal to the preset average particle size difference, the first ratio adjustment coefficient is used to increase the ratio of the lanthanum element to the cerium element;

[0112] If the difference between the average particle size of the rare earth ions and the preset average particle size is greater than the preset average particle size difference, the ratio of the lanthanum element to the cerium element is increased using the second ratio adjustment coefficient;

[0113] In implementation, the ratio of lanthanum to cerium in the test rare earth solution is the percentage of the total mass of lanthanum and cerium to the total mass of the rare earth solution, the preset average particle size difference of the rare earth ions is 0.8 μm, the preset average particle size of the rare earth ions is 2.0 μm, the total mass ratio of lanthanum to cerium is 0.0500%, and the adjustment formula of the total mass ratio of lanthanum to cerium is M=m×αn, Wherein, M is the percentage of the total mass of lanthanum and cerium after adjustment, m is the ratio of lanthanum and cerium before adjustment, α n is the nth ratio adjustment coefficient, α 1 =1.12,α 2 =1.22, if the average particle size of rare earth ions is 2.5 μm, the difference between the average particle size of rare earth ions and the preset average particle size is 0.5 μm, and the ratio of lanthanum to cerium after adjustment is M=m×α n =0.0500%×1.22=0.05600%, that is, if the average particle size of the rare earth ions is 2.5μm, the percentage of lanthanum and cerium increases from 0.0500% to 0.05600%.

[0114] Specifically, the atomic radius of the rare earth lanthanum is 2.74Å, the atomic radius of cerium is 2.7Å, and the atomic radius of iron is 1.72Å. Large-sized rare earth atoms require high energy to dissolve in the crystal lattice by replacing iron atoms, so increasing the percentage of lanthanum and cerium elements can further improve the wear resistance of the high-strength and toughness steel.

[0115] Specifically, the increase in the actual amount of rare earth added is determined by the difference between the preset tensile strength and the tensile strength.

[0116] The process of increasing the actual amount of rare earth added includes:

[0117] If the difference between the preset tensile strength and the tensile strength is less than or equal to the preset tensile strength difference, the actual amount of rare earth added is increased using the first increase coefficient;

[0118] If the difference between the preset tensile strength and the tensile strength is greater than the preset tensile strength difference, the actual amount of rare earth added is increased using a second increase coefficient;

[0119] In practice, the tensile strength is tested using a tensile strength testing machine, the preset tensile strength is 1000MPa, the preset tensile strength difference is 50MPa, the preset rare earth addition amount is 200ppm, and the adjustment formula is T=t×(1+β n ) / 2, where T is the actual amount of rare earth added after adjustment, t is the amount of rare earth added before adjustment, β n is the nth increase coefficient, where β 1 =1.02, β 2 =1.04; if the tensile strength is 980MPa, the difference between the preset tensile strength and the tensile strength is 20MPa, T=t×(1+β n) / 2=200×(1+1.02) / 2=202, that is, when the tensile strength is 980MPa, the actual amount of rare earth added increases from 200ppm to 202ppm.

[0120] Specifically, the rare earth addition amount ranges from 100ppm to 400ppm; wherein the composite rare earth inclusion components include rare earth elements, aluminum oxide and manganese sulfide, and the components of the segregated interface include rare earth elements, lanthanum elements and cerium elements.

[0121] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel, It is characterized in that include: Step S1, applying a rare earth solution for testing to the surface of the alloy steel for rare earth ion penetration and tempering treatment to form a high-strength and toughness steel for testing; Step S2, obtaining an optical image and a segregated interface image of the composite rare earth inclusions on the surface of the high-strength and toughness steel; Step S3, judging whether the anti-corrosion performance of the high-strength and toughness steel meets the standard according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions; Step S4, if it is determined that the anti-corrosion performance does not meet the standard, determining whether to increase the cooling rate in the rare earth ion penetration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions; Step S5, if it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard, then judging whether the wear resistance of the high-strength and toughness steel meets the standard according to the segregation boundary of the lanthanum element in the segregation interface image; Step S6, if it is determined that the wear resistance does not meet the standard, determining the ratio of lanthanum and cerium in the test rare earth solution according to the average particle size of the rare earth ions of the composite rare earth inclusions; Step S7, detecting the tensile strength of the high-strength and tough steel, and determining the actual amount of rare earth added according to the tensile strength of the high-strength and tough steel; Step S8, adding the actual amount of rare earth to the production rare earth solution to perform actual rare earth ion penetration modulation treatment operation on the alloy steel to output high-strength and toughness steel; Judging whether the anti-corrosion performance of the high-strength and toughness steel meets the standard according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions includes: Obtaining the distribution density of rare earth ions in an optical image of the composite rare earth inclusions by scanning electron microscopy; Comparing the distribution density of the rare earth ions with a preset distribution density; If the distribution density of the rare earth ions is greater than the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel meets the standard; If the distribution density of the rare earth ions is less than or equal to the preset distribution density, it is determined that the anti-corrosion performance of the high-strength and toughness steel does not meet the standard; According to the segregation boundary of lanthanum element in the segregation interface image, the wear resistance of high-strength and tough steel is judged to meet the standards, including: The distribution uniformity of the segregation boundary of the lanthanum element was detected by scanning electron microscopy and atom probe to obtain the segregation interface image; Comparing the distribution uniformity of the segregation boundary of the lanthanum element with a preset distribution uniformity; If the distribution uniformity of the segregation boundary of the lanthanum element is greater than the preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel meets the standard; If the distribution uniformity of the segregation limit of the lanthanum element is less than or equal to the preset distribution uniformity, it is determined that the wear resistance of the high-strength and toughness steel does not meet the standard; Determining whether to increase the cooling rate in the rare earth ion infiltration and tempering treatment according to the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions comprises: comparing a difference between a preset distribution density and the distribution density of rare earth ions in the optical image of the composite rare earth inclusion with the preset distribution density difference; If the difference between the preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusion is greater than the preset distribution density difference, then determining to increase the cooling rate in the rare earth ion penetration and tempering treatment; The ratio of lanthanum and cerium in the rare earth solution for testing is determined according to the average particle size of the rare earth ions in the composite rare earth inclusions, including: Collecting the particle sizes of a certain number of sampled rare earth ions on the composite rare earth inclusions; Calculating the average particle size of the rare earth ions according to the particle sizes of the rare earth ions of the plurality of sampled quantities; comparing the average particle size of the rare earth ions with a preset average particle size; If the average particle size of the rare earth ions is greater than the preset average particle size, the ratio of lanthanum to cerium in the rare earth solution for testing is increased; The process of determining the amount of rare earth addition based on the tensile strength of high-strength and tough steel includes: Comparing the tensile strength of the high-strength and toughness steel with a preset tensile strength; If the tensile strength of the high-strength and tough steel is less than or equal to the preset tensile strength, the actual amount of rare earth added is increased.

2. The method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel according to claim 1, It is characterized in that The rare earth ion penetration and conditioning treatment process comprises: Clean the surface of the alloy steel to remove grease and dirt on the surface of the alloy steel; Coating the surface of the alloy steel with a rare earth solution for testing to form a coated alloy steel; Drying the surface of the coated alloy steel to form a fixed coated alloy steel; sequentially heat treating and cooling the fixed coated alloy steel to form high-strength and toughness steel; The rare earth ions in the fixed coating layer have fixed distribution positions.

3. The method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel according to claim 2, It is characterized in that The increase range of the cooling rate in the rare earth ion infiltration and tempering treatment is determined by the difference between a preset distribution density and the distribution density of the rare earth ions in the optical image of the composite rare earth inclusions.

4. The method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel according to claim 3, It is characterized in that The increase range of the ratio of lanthanum element to cerium element in the rare earth solution for testing is determined according to the difference between the average particle size of the rare earth ions and the preset average particle size.

5. The method for controlling the amount of rare earth added to rare earth low alloy high strength and toughness steel according to claim 4, It is characterized in that The increase in the actual amount of rare earth added is determined by the difference between the preset tensile strength and the tensile strength.